Pengaruh Variabel Akuntansi Perusahaan Terhadap Risiko Beta Saham Perusahaan Yang Tercatat di Jakarta Islamic Index Periode 2012-2016 - Ainur Rofiq Kurniawan; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
The goal of this research is to determine the effect of corporate Fundamental Factor on Stock Systematic Risk of Listed Companies in Jakarta Islamic Index (JII) partially or simultaneously. The method of research used is the quantitative approach. The sample of the research is are 13 companies registered in Jakarta Islamic Index that meet the criteria of purposive sampling. The analysis technique used best estimation model by Common Effect Model (CEM) and the result is Y = 0,616495 + 0,002389CRit + 0,006740DERit - 0,028809ROAit - 0,017486PERit and R2 13,58%. The result of the partial test shows that Current Ratio and Debt to Equity ratio has a significant effect. The result of the simultaneous test shows that the four variables have significant effects in company stock beta registered in Jakarta Islamic Index.   REFERENCESAnoraga, Panji dan Panji Pakarti. 2001. Pengantar Pasar Modal. Edisi Revisi. Jakarta: PT Rineka Cipta.Bergevin, Peter M, 2002, Financial Statement Analysis, New Jersey; pretince HallHartono, Jogiyanto, 1998, Teori Portofolio dan Analisis Investasi. Edisi pertama. BPFE.YogyakartaJones, Charles O. 1996. Pengantar Kebijakan Publik (Public Policy. Terjemahan Rick Ismanto.Jakarta: RajaGrafmdo Persada.Jones, Charles P., 2004, Investment, New York : Prentice-Hall.Kieso, Donald E., Jerry J. Weygandt, dan Terry D. Warfield, 2002. Akuntansi Intermediete, Terjemahan Emil Salim, Jilid 1, Edisi Kesepuluh, Penerbit Erlangga, Jakarta.Munawir, S. 2002. Analisis Laporan Keuangan. Edisi Ketujuh. Yogyakarta: Liberty.Weston, J. Fred dan Thomas E. Copeland. 1995. Manajemen Keuangan I. Edisi Kesembilan. Penerbit Binarupa Aksara. Jakarta.